2015
DOI: 10.1063/1.4932154
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of the levelized cost of tidal, wave, and offshore wind energy

Abstract: In the current context of environmental degradation and depletion of fossil fuels, marine energy has emerged as an alternative to traditional energy resources. However, being in an initial step of development, extracting energy from the ocean is often regarded as difficult and uneconomical. The existing models for assessing marine energy costs are often oversimplified, leading to uncertainties that may hold investors back and slow down the market penetration of this renewable. Therefore, an accurate prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 66 publications
0
33
0
1
Order By: Relevance
“…Moreover, the power transmission options and specific problems for MRE converter farms (e.g., the multitude of the subsea components operating in harsh environments) have been analytically discussed in [56] along with some optimization schemes considering as a test case the Pelamis P1 device; see also [45,57]. The status of wave energy progress in Europe has been described in [58], while an overview of the wave energy economics can be found in [59,60]. An account of multiple aspects as regards wave energy, including wave energy resource, economics, and technology of WECs, has been provided in [40].…”
Section: Sea Testing Experience In Several European Test Centers (Danmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the power transmission options and specific problems for MRE converter farms (e.g., the multitude of the subsea components operating in harsh environments) have been analytically discussed in [56] along with some optimization schemes considering as a test case the Pelamis P1 device; see also [45,57]. The status of wave energy progress in Europe has been described in [58], while an overview of the wave energy economics can be found in [59,60]. An account of multiple aspects as regards wave energy, including wave energy resource, economics, and technology of WECs, has been provided in [40].…”
Section: Sea Testing Experience In Several European Test Centers (Danmentioning
confidence: 99%
“…In [236], the increase of the load factor and material efficiency, and the decrease of decommissioning costs have been suggested, the author in [237] has concluded that the price of offshore wind power expansion is reasonable and that the support scheme with incentives and enforcement of efficiency improvement proved to be successful, while in [238], scenarios regarding cost reduction of renewable energy in the EU scale have been presented and discussed. The levelized costs of tidal, wave, and offshore wind energy have been evaluated and compared in [60].…”
Section: The Economics Of Offshore Renewablesmentioning
confidence: 99%
“…The agreement is due to enter into force in 2020. In this context, marine energy [1] emerges as one of the most promising alternatives to fossil fuels due to its substantial potential for electricity production [2], not least through the combination of various renewables in the same marine space [3], which can significantly enhance marine energy competitiveness [4]. Co-located projects are a solution to simultaneously tackle two major challenges: reducing technology costs [5] and achieving a more sustainable use of natural resources [6].…”
Section: Introductionmentioning
confidence: 99%
“…The LCoE is the ratio of total lifetime expenses versus total expected outcomes, expressed in terms of the present equivalent value (including discount rates), representing the cost at which electricity must be generated to reach the breakeven point over the lifetime of the project. Astariz et al 10 reported that the LCoE values of wave (325e/ MW h), tidal (190e/MW h), and offshore wind (165e/MW h) energy are approximately three to five times more than those of conventional energy sources, which highlights the importance of increasing public funding to attract investors either in the R&D stages of the technologies or through feed-in tariffs and subsidies. Those high LCoE values are expected to decrease significantly in the future as a result of investment in R&D, which will continuously advance the technology toward commercial viability.…”
Section: Marine Renewable Energymentioning
confidence: 99%